Beyond Barriers: Fostering Inclusive Classrooms for Every Student - Akhmedova, Zulfiya (The Lingua Spectrum, 2024)
This thesis explores the transformative approach of inclusive education, which promotes the integration of all students, including those with disabilities, into mainstream educational settings. Grounded in principles of equity and respect for diversity, it asserts that all students have the right to quality education. The study examines foundational principles of inclusive education, its benefits, the challenges faced during implementation, and strategies for fostering an inclusive environment. Key findings highlight the importance of individualized support, collaborative learning, and effective policy development. While inclusive education enhances academic outcomes and social skills, challenges such as teacher preparedness, resource allocation, and societal attitudes must be addressed. By advocating for comprehensive training and community engagement, this thesis underscores the necessity of creating supportive educational environments that embrace diversity and promote the success of all learners.